Comprehensive Analysis of Different Contemporary Barley Genotypes Enhances and Expands the Scope of Barley Contributions to Beer Flavor. (1st July 2021) - Windes, S.; Bettenhausen, H. M.; Simaeys, K. R. Van; Clawson, J.; Fisk, S.; Heuberger, A. L.; Lim, J.; Queisser, S. H.; Shellhammer, T. H.; Hayes, P. M.
Abstract: Recent research has demonstrated contributions of barley genotype to beer flavor based on the progeny of a cross between an heirloom and a more contemporary barley variety. To advance this line of research, the current study used two independent sets of barley germplasm to address the contributions of different barley genotypes to beer flavor. Pedigree, quality of malt and beer, and beer metabolomic profiles were compared within and between the two sets. Utilizing both laboratory and consumer panels, differences in sensory attributes of malt hot steeps and lager beers that are attributable to barley genotype were investigated. Genotype, in this context, is defined in the broadest sense to include experimental germplasm and released varieties. Results concur with previous studies: the two sets of barley germplasm were found to have, both within and between, distinct but subtle differences in flavor profiles of malt hot steeps and finished lager beers. Distinct metabolomic profiles, attributable to barley genotype, were detected. Further, covariation of metabolomic profiles and sensory attributes were identified using data from both sensory panels. These observations lead to the conclusion that the variable metabolites observed among the two sets of barley germplasm are a direct result of genetic differences that lead to differential chemical responses within the malting and brewing processes.